Kecerdasan Sosial dalam Ca’-oca’an Madura: Kajian Hermeneutik Bersusun - Makki, M. Ismail; Aflahah, Aflahah; Albaburrahim, Albaburrahim (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research examines proverbs in the Madurese ethnic community with a focus on proverbs Ca'oca'an which have a relationship with social intelligence. The construct of social intelligence used is five dimensions according to Albreht, namely situational Awareness, Presence, Authenticity, Clarity and Emphaty. The research method used is tiered hermeneutic. The results showed that five Madurese ca'oca'an were found which reflected social intelligence which prohibited Madurese as a guide in establishing social interaction so that they had a high level of social intelligence, namely Taoh Tèngka, Jijib, Seduhuna, Jhârna' and Andi' Atè.